2013
DOI: 10.3892/etm.2013.892
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a tumor-associated gene, LASS2, in the human bladder carcinoma cell lines BIU-87, T24, EJ and EJ-M3

Abstract: Homo sapiens longevity assurance homolog 2 of yeast LAG1 (LASS2), a metastasis suppressor gene of human cancer, is the most abundantly expressed member of the ceramide synthase gene family. Expression of LASS2 has been reported in carcinomas of the prostate, liver and breast. However, there has been no report on the expression of LASS2 in human bladder cancer cell lines. In order to investigate the expression and potential role of this new tumor metastasis supressor gene in human bladder cancer, we compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Our previous study demonstrated that LASS2-negative bladder cancer was associated with poor clinical prognosis [29]. LASS2 downregulation leads to enhanced ability of proliferation and invasion in bladder cancer cells [30]. In addition, LASS2 enhances chemosensitivity of breast cancer by counteracting acidic tumor microenvironment through inhibiting activity of VATPase proton pump and IAP signaling pathway [19], which suggests LASS2 may regulate Bcl-2 and survivin expression.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous study demonstrated that LASS2-negative bladder cancer was associated with poor clinical prognosis [29]. LASS2 downregulation leads to enhanced ability of proliferation and invasion in bladder cancer cells [30]. In addition, LASS2 enhances chemosensitivity of breast cancer by counteracting acidic tumor microenvironment through inhibiting activity of VATPase proton pump and IAP signaling pathway [19], which suggests LASS2 may regulate Bcl-2 and survivin expression.…”
Section: Discussionmentioning
confidence: 98%
“…RT-qPCR was conducted according to previously described methods ( 11 ). Briefly, total mRNA was extracted using TRIzol (Invitrogen) and purified.…”
Section: Methodsmentioning
confidence: 99%
“…Western blot assays were performed according to previously described methods ( 10 , 11 , 13 ). Briefly, cMSCs were lysed with RIPA buffer containing phenylmethylsulfonyl fluoride (Sangon Biotech Co., Ltd.), then 50 µg total protein was quantitated using a BCA protein assay kit (P0009; Beyotime Institute of Biotechnology) and subjected to 6–10% SDS-PAGE.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, an implantation metastasis model of the highly invasive human bladder cancer EJ-M3 cell line was established in nude mice ( 11 , 12 ). Another study identified that LASS2 expression was the highest in the EJ-M3 cell line compared with other human bladder carcinoma cell lines (BIU-87, T24 and EJ), and was significantly correlated with the proliferation, metastasis and invasion of human bladder cancer ( 13 ). In the present study, EJ-M3 cells were selected for a lentivirus-mediated LASS2 interference strategy and LASS2 overexpression, in order to investigate the effects of LASS2 expression on bladder cancer cell tumorigenicity and growth in vitro and in nude mice.…”
Section: Introductionmentioning
confidence: 99%